THE IMPLEMENTATION CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) IN SPEAKING CLASSES AT UIN SAYYID ALI RAHMATULLAH TULUNGAGUNG - Anindita Badianti; Baiq Sumarni; Enggar Larasati (Jurnal Bahasa Lingua Scientia, 2025)
Content and Language Integrated Learning (CLIL) is increasingly regarded as an effective approach in fostering both language and content knowledge simultaneously. While numerous studies emphasize its application in various educational contexts, there remains a significant gap concerning its implementation in higher education, particularly in speaking classes. This qualitative study investigates the implementation of CLIL in 5 speaking classes at UIN Sayyid Ali Rahmatullah Tulungagung, with particular attention to pedagogical practices, challenges, and learners’ perceptions. Data were collected through classroom observations, semi-structured interviews, and document analysis. The results indicate that although CLIL enriches communicative competence, various challenges such as limited material, teacher preparedness, and student readiness persist. The findings offer insights into improving speaking instruction and enhancing the integration of content and language in tertiary education.